P368 Epileptiform and sleep spindle activity in anterior nucleus of the thalamus in temporal lobe epilepsy patients. Issue 9 (September 2017) - Jordan, Zsofia; Virag, Marta; Hajnal, Boglarka; Bodizs, Robert; Ujma, Peter; Kelemen, Anna; Halasz, Laszlo; Entz, Laszlo; Fabo, Daniel; Eross, Lorand
Abstract : Introduction: Deep brain stimulation of anterior nucleus of the thalamus (ANT-DBS) is an approved therapeutic approach for drug resistant epilepsy. Little is known about the participation of ANT in epileptic and sleep EEG processes. The appearance of the sleep spindles (SS) is related to interictal discharges (IID), and thalamus is considered as the generator of SSs, however, according to animal data, ANT do not participate in the genesis of sleep spindles. Methods: In this present study we included 10 ANT-DBS bitemporal epilepsy patients with externalised leads and surface electrodes undergoing 2 days video-EEG monitoring (VEM). We investigated IIDs, ictal events (IE) and SSs in ANT and also in surface EEG recordings. IIDs and IEs were analysed by visual inspection, SSs were detected according to the patient own special spindle frequency, separately on the scalp (Fp1-2, F3-4, F7-8) and thalamus both sides. SS spectral peak frequency and synchronization between scalp and ANT was measured. Results: IIDs appeared in the thalamus and on the scalp both dependent and independent manner. Three patients had seizures during VEM. Seizures did not start but start spread to the ANT electrodes. The slow, frontal type of SSs were prevailing in the ANT. Conclusion: ANT participates in both sleep and epileptogenic processes. It seems that IIDs and IE spread to the ANT. Frontal, slow frequency SSs has local sources int he ANT indication its participation in sleep processes. Further evaluation for seizure outcome of ANT-DBS therapy and correlation with ANT recordings are underway.